AGE-RELATED DIFFERENCES IN THE CLINICAL PROFILE AND OUTCOMES OF ACUTE CORONARY SYNDROME - Ishtiyaq Masood; Haider Rashid (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The most common presentation of coronary artery disease (CAD) is acute coronary syndrome (ACS). The clinical profile of young patients with CAD can differ significantly from that of older patients. Our study aimed to assess the clinicoangiographic profile and In-hospital outcomes of patients presenting with acute coronary syndrome (ACS) to our centre. This study was a single-centre retrospective study. We analysed the medical records of the patients presenting with acute coronary syndrome (ACS) to our hospital for two years between 01.01.2022 and 01.01.2024. Obesity, smoking, family history of premature coronary artery disease (CAD), and substance abuse were common risk factors of acute coronary syndrome (ACS) in younger populations. Hypertension and diabetes mellitus were the most common risk factors in older patients. Anterior wall myocardial infarction was the most common presentation of ACS in young patients. The most common CAD pattern on coronary angiography was single-vessel disease (SVD). The outcomes of younger patients were better.